(untitled) (International Journal of Food and Nutritional Sciences, 2017)
The Constitution of India is the preeminent rule that offers a vessel enabling Justice, Liberty, Equality, Freedom and Fraternity upon India as unalienable qualities, which gives the nation a democratic and social balance. The Constitution of India forbids inequality depending on gender yet it similarly guides and enables the administration to protect and manipulate the uncommon measures for women. Despite the fact that the situation for women has enhanced over the most recent four decades, yet Indian women are confronting the hardest time rationally and physically, mostly because of ignorance and absence of learning of lawful and established tools of patriarchy in gender based inequality This paper discusses the types of violence committed against women and a general preface of structures of violence along with the probable measures that can relatively aid the abused against the abuser.